Effect of soil amendment with activated yeasts on controlling Fusarium and Verticillium wilt and growth characters of pepper - El-Fawy, M. M.; Ahmed, M. M. S. (Journal of Phytopathology and Disease Management, 2015)
Wilt disease of pepper caused by Fusarium oxysporum f. sp. capsici (FOC) and Verticillium dahliae (VD) is serious worldwide disease and cause great problems in all pepper production areas of the world. Six isolates of FOC and three isolates of VD were obtained from naturally diseased pepper plants from different localities of Assiut Governorate, Egypt. These isolates had the ability to cause wilt symptoms either as a vascular browning or as a foliar yellowing with different degrees. Also, there was correlation between the degree of vascular browning and foliar yellowing which has occurred with the same tested isolate. The efficacy of activated yeasts of Saccharomycess cerevisiae (dry and soft) for controlling the wilt disease caused by FOC and VD was studied. In greenhouse experiments, application of dry and soft activated yeast at the concentrations of 4, 6 and 8 gL-1 into infested soil with FOC and VD one and three weeks after seedlings transplanting significantly reduced the disease severity of Fusarium and Verticillium wilts. Likewise, concentration of 6 gL-1 of yeasts was the most effective ones. Data indicated that the soft yeast treatment exhibited the highest reduction in the disease severity compared to other treatments in both tested seasons (2014 and 2015). Yeasts treatments significantly enhanced stem length and diameter of pepper plants compared to untreated plants.Â